Improving spun yarn properties by contacting fiber strand with special-shape condensed surfaces. Issue 11 (26th October 2022) - Xu, Duo; Su, Ziyi; Fan, Hang; Yang, Wangwang; Fang, Jian; Liu, Keshuai; Xu, Weilin
Abstract: A theoretical analysis on the key mechanisms of fiber control on special-shaped condensed surfaces was conducted. The intervention of synergistic effects from narrow condensed, inclined contact, and static arc surfaces can agglomerate the strand fibers and enhance fiber transfer to control fiber motion. The losing fiber can be captured on the yarn surface to improve yarn weak links without any fiber accumulations, while local-exposed fibers can be rewrapped into the yarn body to strengthen the fiber utilization rate. Experimental results confirmed that yarn hairiness was significantly reduced by contacting special-shaped condensed surfaces in the yarn formation area. The irregularity results showed a slight deterioration after applying the special-shaped condensed surfaces, resulting from the friction between the strand and surfaces. Moreover, the tensile strength of the special-shaped condensed surface-spun yarn showed considerable improvement owing to the increased fiber utilization rate. The experimental results correspond well to the theoretical analysis.